ENERGY EFFICIENT RESOURCE MANAGEMENT IN CLOUD COMPUTING BY LAOD BALANCING AND AUTO SCALING (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing can lessen electricity intake through the usage of virtualizedcomputational sources to provision an application’s computational sources on demand. Autoscalingis an essential cloud computing method that dynamically allocates computationalsources to programs to healthy their modern hundreds precisely, thereby eliminating sourcesthat could in any other case stay idle and waste electricity. This paper affords a model-pushedengineering method to optimizing the configuration, strength intake, and running fee of cloudauto-scaling infrastructure to create greener computing environments that lessen emissions onaccount of superfluous idle sources. The paper presents 4 contributions to the take a look atof model-pushed configuration of cloud auto-scaling infrastructure through explaining howdigital system configurations may be captured in function fashions, ( describing how thosefashions may be converted into constraint pleasure problems (CSPs) for configuration andstrength intake optimization, displaying how greatest auto-scaling configurations may bederived from those CSPs with a constraint solver, and providing a case take a look atdisplaying the strength intake/fee discount produced through this model-pushed method.